On Interaction Between Mode III Crack and a Nonideal Bimaterial Interface - Mishuris, G.S. (Engineering Transactions, 1997)
Behaviour of a stress field in a neighbourhood of a crack tip placed near a nonideal interface is investigated. Along the interface tractions are continuous, but displacements are assumed to be discontinuous, and proportional to the tractions. Coefficient of proportionality depends on a geometrical form of the interfacial zone.